306 GERIATRICIAN-LED COMPREHENSIVE GERIATRIC ASSESSMENT IN THE EMERGENCY DEPARTMENT: A COST-EFFECTIVE SERVICE APPROVED BY PATIENTS. (25th October 2022) - Magner, S; Carey, S; Harrington, G; Ward, L; Smyth, H; Purcell, R; Callaly, L; O'Caheny, C; Pender, C; Buckley, B; Laguna, R; Riches, R; et al.
Abstract: Background: Many older people are brought to the Emergency Department (ED) who do not require acute hospital admission but there are risks to these patients if this occurs. The Frailty Intervention Team (FIT) are an interdisciplinary team based in the ED including physiotherapy, occupational therapy, speech and language therapy, dietetics, pharmacy, advanced nurse practitioners, and a geriatric registrar and consultant. They assess frail older patients and suggest alternative care pathways to admission. We aimed to investigate the impact of FIT on admission avoidance, bed days saved and to obtain patient feedback on their experience. Methods: Routinely collected data from May 2021 to April 2022 was reviewed retrospectively. An anonymous patient feedback questionnaire was posted to 40 patients randomised from the FIT worklist between January to May 2022. Results: 2, 025 Comprehensive Geriatric Assessments (CGA) were completed between May 2021 and April 2022. 38% percent of patients were discharged home, 45% of this number had follow-up arranged. 104 patients were transferred directly to an offsite bed, mostly rehabilitation. We estimate we avoided 51 admissions to the acute hospital per month, almost half of these were patients admitted to the hospital and, who we discharged to alternative care pathways or home. The average length of stay in April 2022 was 22 days – by avoiding 615 admissions between May 2021 and April 2022 we have saved 13, 530 bed days at an estimated cost saving of almost €11 million. 15 completed questionnaires were returned. 73% were very satisfied with their experience. 87% felt the FIT team helped facilitate their discharge from ED. The main themes identified from open ended questions included thorough assessment, patient centred care and satisfaction with early intervention and discharge. Conclusion: A Frailty Intervention Team is a cost effective and patient centred way of avoiding unnecessary admissions for older people presenting to the ED.